Anti-Inflammatory and α-Glucosidase Inhibitory Activities of Chemical Constituents from Bruguiera parviflora Leaves - Tung Thanh Bui; Khanh Phuong Thi Nguyen; Phung Phi Kim Nguyen; Dung Tien Le; Thuy Le Thi Nguyen (Journal of Chemistry)
Bruguiera parviflora (Rhizophoraceae) is one of the Bruguiera genus-based mangrove plants which has not been investigated for the chemical compositions as well as biological activities so far. The present study was aimed at investigating the phytochemicals as well as anti-inflammatory and α-glucosidase inhibitory activities of B. parviflora leaves. The results showed that the crude extract and its fractions significantly increased the percentage inhibitory activity against α-glucosidase and decreased NO production in LPS-stimulated RAW 264.7 cells in a dose-dependent manner. The most effective fraction BP5 was further chromatographed and purified. As a result, eight compounds were isolated and elucidated, including five flavonoids (1–5) and three triterpenoids (6–8). All isolated compounds were evaluated for the anti-inflammatory and α-glucosidase inhibitory effects. The results indicated that flavonoids namely taxifolin (1), quercetin (2), myricetin (3), rutin (4), and kaempferol (5) exhibited potent anti-inflammatory as well as α-glucosidase inhibitory activities. Among them, compound 2 showed the most potent inhibitory effect against an α-glucosidase activity with an IC50 value of 3.4±0.5 μg/mL and the LPS-induced NO production of 11.8 μM at the concentration of 100 μg/mL. These findings suggest that flavonoids (1–5) from B. parviflora leaves may be useful as the potential α-glucosidase inhibitor as well as anti-inflammatory agent.